2012
DOI: 10.2134/jeq2011.0277
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Cattle Grazing Affects Pasture Litter-Fall: An Unrecognized Nitrous Oxide Source

Abstract: The rationale for this study came from observing grazing dairy cattle dropping freshly harvested plant material onto the soil surface, hereafter called litter-fall. The Intergovernmental Panel on Climate Change (IPCC) guidelines include NO emissions during pasture renewal but do not consider NO emissions that may result from litter-fall. The objectives of this study were to determine litter-fall rates and to assess indicative NO emission factors (EFs) for the dominant pasture species (perennial ryegrass [ L.] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The soil at both sites was a strongly gleyed, Temuka clay loam (Typic Orthic Gley; [Hewitt 1998]) with impeded subsoil drainage. The pasture species included perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) which were regularly grazed by dairy cows as previously described (Pal et al 2012). To avoid the antecedent excreta effects of grazing animals, pasture areas (15 × 20 m) were fenced and animals excluded for six months prior to commencing the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil at both sites was a strongly gleyed, Temuka clay loam (Typic Orthic Gley; [Hewitt 1998]) with impeded subsoil drainage. The pasture species included perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) which were regularly grazed by dairy cows as previously described (Pal et al 2012). To avoid the antecedent excreta effects of grazing animals, pasture areas (15 × 20 m) were fenced and animals excluded for six months prior to commencing the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Pasture leaf tissues may contribute to N 2 O emissions. For example, plant material harvested, but not ingested, by dairy cattle falls to the soil surface where up to 1% of the embodied N may be released as N 2 O (Pal et al 2012(Pal et al , 2013. The following study was designed to examine the potential for pasture-N to contribute to N 2 O emissions following animal treading.…”
Section: Introductionmentioning
confidence: 99%
“…The model assumed that cows consumed 55% of available foliage (Pal et al, 2012) at each grazing event. If grazing was spread over several consecutive days, grazing percentages on individual days were adjusted to add to a total of 55%.…”
Section: Modelling Detailsmentioning
confidence: 99%
“…During a grazing event, cows can graze paddocks from a pre-grazing pasture cover of up to 3000 kgDW ha −1 and ingest up to 1650 kgDW ha −1 (assuming 55% of available feed being ingested; Pal et al, 2012). Assuming a carbon content of 50%, this equates to an intake of up to 825 kgC ha − 1 d − 1 .…”
Section: Ecosystem Respiration-challenges Posed By Grazing Eventsmentioning
confidence: 99%
“…Previous results using 15 N to apportion N 2 O sources have shown that emissions from plant residue applications can be short-lived (Frimpong and Baggs, 2010;Frimpong et al, 2011). Ruminant grazing of pasture and forage crops causes fresh litterfall, as animals fail to ingest all harvested herbage (Lodge et al, 2006;Campanella and Bisigato, 2010;Pal et al, 2012). One study, replicating a grazing-induced litterfall event, used 15 N tracer to show that fresh litter deposition contributed to the N 2 O flux (1% of N applied) from the soil surface and enriched the soil inorganic-N pool (Pal et al, 2013).…”
Section: Stable Isotopes Of Nitrogenmentioning
confidence: 99%